The spectra and energies of classical double radio lobes - Blundell, K; Rawlings, S (IOP Publishing, 2000)
We compare two temporal properties of classical double radio sources: (1) radiative lifetimes of synchrotron-emitting particles and (2) dynamical source ages. We discuss how these can be quite discrepant from one another, rendering use of the traditional spectral aging method inappropriate: we contend that spectral ages give meaningful estimates of dynamical ages only when these ages are Lt 107 yr. In juxtaposing the fleeting radiative lifetimes with source ages that are significantly longer, a refinement of the paradigm for radio source evolution is required. We move beyond the traditional bulk backflow picture and consider alternative means of the transport of high Lorentz factor (γ) particles, which are particularly relevant within the lobes of low-luminosity classical double radio sources. The changing spectra along lobes are explained, not predominantly by synchrotron aging but by gentle gradients in a magnetic field frozen into a low-γ matrix that illuminates an energy distribution of particles, N(γ), controlled largely by classical synchrotron loss in the high magnetic field of the hot spot. A model of a magnetic field whose strength decreases with increasing distance from the hot spot and in so doing becomes increasingly different from the equipartition value in the head of the lobe is substantiated by constraints from different types of inverse Compton scattered X-rays. The energy in the particles is an order of magnitude higher than that inferred from the minimum energy estimate, implying that the jet power is of the same order as the accretion luminosity produced by the quasar central engine. This refined paradigm points to a resolution of the 1994 findings of Rudnick et al. and Katz-Stone and Rudnick that both the Jaffe-Perola and Kardashev-Pacholczyk model spectra are invariably poor descriptions of the curved spectral shape of lobe emission and, indeed, that for Cygnus A all regions of the lobes are characterized by a "universal spectrum."